Manual de boas práticas em internamento de cães e gatos - Pazzim, Aline Fantinel (My University, 2023)
The practice of medicine within the hospitalization sector for dogs and cats, in addition to requiring a lot of attention to clinical conduct, also pays attention to the various details and safety and nursing protocols, optimizing the treatment of our patients. In human medicine, there are extensive and detailed materials describing and discussing various care with hospitalized patients and standardization of steps, whereas in veterinary medicine, the literature is still scarce. The importance of standardizing health-related activities is known, due to the optimization of patient treatment, reduction of hospitalization time, in addition to avoiding accidents with the professional or patient and reducing the cost of veterinary hospital services. Veterinary medicine is constantly evolving, and we must work together to bring relevant and up-to-date information to a greater number of professionals in the field, which will improve the outcomes of our patients. The objectives of this work were to identify critical points and updated needs in hospitalization, to develop a guide for conduct in the hospitalization of dogs and cats and to disseminate it to the veterinary community, to stimulate the development of complementary literature on this subject, to register the procedures and conducts of veterinary teams, improve patient outcomes and safety. As a methodology, a virtual questionnaire sent through social networks and instant messaging applications to veterinarians in Rio Grande do Sul, personal technical experience of the authors and collaborators and theoretical reference for the basis and preparation of the manual was used. [resumo fornecido pelo autor]
A prática da medicina dentro do setor de internação de cães e gatos além de requerer muita atenção para as condutas clínicas, também dispensa atenção para os vários detalhes e protocolos de segurança e enfermagem, otimizando o tratamento dos nossos pacientes. Na medicina humana existem amplos e detalhados materiais descrevendo e discutindo diversos cuidados com pacientes internados e padronizações de etapas, já na medicina veterinária a literatura ainda é escassa. Sabe-se da importância da padronização das atividades ligadas à saúde, devido a otimização do tratamento do paciente, redução do tempo de internação, além de evitar acidentes com o profissional ou paciente, e reduzindo o custo de serviço hospitalar veterinário. A medicina veterinária está em constante evolução, e devemos trabalhar juntos para levar a um maior número de profissionais da área, informações relevantes e atualizadas, que melhorem os desfechos dos nossos pacientes. Este trabalho teve como objetivos a identificação de pontos críticos e necessidades atualizadas em internamento, desenvolver um guia de condutas em internamento de cães e gatos e difundir para a comunidade veterinária, estimular o desenvolvimento de complementação de literatura neste assunto, protocolar os procedimento e condutas das equipes veterinárias, melhorar os desfechos e segurança dos pacientes. Como metodologia foi utilizado um questionário virtual enviado através de redes sociais e aplicativos de mensagens instantâneas para médicos veterinários do Rio Grande do Sul, experiência técnica pessoal dos autores e colaboradores e referencial teórico para embasamento e confecção do manual. [resumo fornecido pelo autor]
Keywords: Animais - Doenças; Medicina veterinária de pequenos animais; Hospitalização; Enfermagem; Medicina veterinária; Animals - Diseases; Pet medicine; Hospitalization; Nursing; Veterinary medicine